Peranan Diklat Penerbangan STPI – Curug Untuk Memenuhi Kebutuhan Pilot Pesawat Udara di Indonesia - Yuke Sri Rizki (Research and Development Agency of The Ministry of Transportation, 2011)
Recently, the national air transportation experiencing significant growth include the increasing number of airlines in operation and the number of passengers carried. The impact of these developments, one is the increase in aircraft operations and should be supported by human resources in these field including the pilot.Pilot needs to reach 400 people per year have not been fulfilled by the product all the existing flying school. Based on this, conducted a study to observe the implementation of Pilot Training at STPI-Curug with a view to providing input to improve the quality and quantity of graduates majoring in flight.Analysis and discussion in this study using qualitative methods, using both oral and written data obtained from respondents and observations, described in detail, relating to cause and effect that produced a recommendation to the purpose of the study.